2021
DOI: 10.13057/biodiv/d221119
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Fish diversity and its relationship with environmental variables in Kamala River, Nepal

Abstract: Ghimire S, Koju NP. 2021. Short Communication: Fish diversity and its relationship with environmental variables in Kamala River, Nepal. Biodiversitas 22: 4865-4871. Kamala River originates from the lower part of the Mahabharat range and flows through inner to outer Terai, providing a broad range of ecosystem services; provisioning, regulating, supporting, and cultural. However, the information regarding the environmental factors and species diversity in the river is not available enough. Hence the study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
4
4
0
Order By: Relevance
“…Nutrients and pH exerted little influence on fish abundance and diversity in the river. These results concur with the findings of Ghimire and Koju (2021), Wu et al. (2011) and Suvarnaraksha et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nutrients and pH exerted little influence on fish abundance and diversity in the river. These results concur with the findings of Ghimire and Koju (2021), Wu et al. (2011) and Suvarnaraksha et al.…”
Section: Discussionsupporting
confidence: 93%
“…These results concur with the findings ofGhimire and Koju (2021),Wu et al (2011) andSuvarnaraksha et al (2012) who studied the relationship of fish species diversity and environmental variables in Kamala River (Nepal), Chisui River (China), and a tropical river in Ping-Wang River Basin (Thailand), respectively, and reported strong correlation between fish species diversity and temperature, dissolved oxygen, channel velocity, electrical conductivity, TDS and nitrates. The physico-chemical parameter ranges observed in this study compare favourably to the findings ofOuma et al (2016) andOrina et al (2017) in similar water quality studies of Lake Victoria and River Kuja, respectively.…”
supporting
confidence: 91%
“…The highest species richness and diversity observed at the mouth of the river may be attributed to the influence of the lake and the general trend of increased species richness and diversity downstream [3]. The fish species diversity observed in the Awach Kibuon River (21 species, 12 genera, 7 families and 6 orders) is comparable to that reported in Kamala River in Nepal of 19 species belonging to 15 genera, 8 families and five orders [9] and the 23 species in 7…”
Section: Pan Africa Science Journalmentioning
confidence: 51%
“…The significant positive correlation between fish species richness and temperature, depth, conductivity, and total dissolved solids in the Awach Kibuon River is similar to the findings of several previous studies. A study on fish diversity and its relationship with environmental variables in Kamala River, Nepal [9] reported that species variation was correlated with temperature, electrical conductivity, TDS, and nitrate. Another study in the Chishui River, a protected tributary of the Yangtze River (China), [45] found that altitude, conductivity, dissolved oxygen, channel width, and current velocity significantly influenced the structure fish assemblages.…”
Section: Relationships Between Fish Species Diversity and Physico-che...mentioning
confidence: 99%
“…The Redundancy Analysis (RDA) ordination method revealed that species variation was correlated with temperature, Electrical Conductivity (EC), Total Dissolved Solids (TDS), and nitrate. Nonetheless, different river sections were disturbed due to mining, deforestation, and construction activities, which could pose a real threat to fish diversity and population, and other aquatic organisms [10].…”
Section: Introductionmentioning
confidence: 99%